Representations of New Public Management in Australian Public Service gender equality policies. Issue 2 (23rd January 2020) - Williamson, Sue; Carson, Lisa; Foley, Meraiah
Abstract : Purpose: Governments have demonstrated a renewed interest in progressing gender equality for their workforces, including in Australia. This refocusing has resulted in a tranche of new gender equality policies being introduced into the Australian Public Service (APS). The purpose of this paper is to examine how New Public Management (NPM) is reflected in these gender equality policies and consider whether NPM may assist or hinder gender being "undone" or "redone" in APS organisations. Design/methodology/approach: A content analysis was conducted to assess the strategies contained within the gender equality policies of all 18 Australian government departments. Findings: The content analysis reveals that the policies strongly reflect an NPM framing, except in one important area – that of monitoring and evaluation. The lack of attention to this crucial element of NPM may hinder effective implementation of many of the policies. The authors also conclude that while good intent is evident in the policies, they may "redo" rather than "undo" gender in organisations. Practical implications: The paper will assist organisations which are developing and implementing gender equality policies. Even though NPM is specific to the public sector, the research highlights the potential and pitfalls when developing such policies in an environment focused on increasing efficiencies and reducing costs. Originality/value: While gender equality and public sector reforms occurred simultaneously in Australia, few researchers have examined the interactions between the two.